Ureteral clipping for the treatment of a non-functioning upper kidney moiety associated with a massive ureterocele: step-by-step description of a novel technique. Issue 3 (May 2019) - Lopes, R.I.; Mello, M.F.; Koyle, M.A.; Lorenzo, A.J.
Summary: Objective: The objective of this video is to illustrate feasibility of the ureteral ligation for the treatment of massive ureteroceles associated with non-functioning upper kidney moieties in duplex kidneys. Materials and methods: In this video, one case is presented to demonstrate this novel technique. A nine-year-old boy presented with progressive lower urinary tract symptoms. Radiological workup depicted a duplex kidney on the left side with the absence of function on the upper pole and hydroureteronephrosis with a massive ureterocele. Laparoscopic ureteral transection, drainage, and ligation of both extremities of the enlarged ureter (upper pole ureter) were performed. Results: Immediately after ureteral ligation, ultrasonic evidence of ureterocele decompression and improved hydroureteronephrosis was observed. This patient remained asymptomatic without postoperative complications after 3 years. De novo reflux was not observed. Conclusion: Ureteral ligation, as demonstrated in the video, is a good approach for the treatment of massive ureteroceles associated with non-functioning upper kidney moieties in duplex kidneys. Compared with the current standard techniques (incision/puncture), ureteral ligation has the clear advantage of not causing 'de novo reflux' or unsuccessful de-obstruction, and is not as surgically demanding as other reconstructive/ablative techniques. The disadvantage is the need of regular clinical and ultrasonographic follow-up.